Type 1 Diabetes Mellitus And Associated Morphological Alterations In The Permanent Dentition –A Cross Sectional Study (International Journal of Environmental Sciences, 2025)
Background: Type 1 Diabetes Mellitus (T1DM) is an endocrinal disorder caused by the autoimmune destruction of beta cells of pancreas. It occurs more commonly in younger age group and hence termed as juvenile diabetes. Odontogenesis is the complex process of tooth formation involving genetic, epigenetic and environmental factors to control the interaction between epithelium and ectomesenchyme. Our study aimed to know the effect of T1DM on the odontogenic apparatus. Methodology and Results: 39 T1DM patients were taken for the study and their dental morphology was recorded using alginate impression material. Out of 39 patients, 8 were aged less than or equal to 6 years and presented with only deciduous dentition. The remaining 31 T1DM (N=31) patients were included in the study and the morphology of their permanent dentition was studied. Gender matched subjects less than 20 years of age without diabetes mellitus were taken as controls and their morphology was recorded. On comparison, 61% (n=19) of the T1DM patients showed dental anomalies, in contrast to 12.9 % (n=4) of the controls. Sixth cusp in mandibular molars, multiple prominent grooves, pits and fissures on the occlusal surfaces of molars and premolars, enamel hypoplasia were the commonly observed anomalies. Conclusions: T1DM influence odontogenesis through systemic effects like hyperglycemia, chronic inflammation and vascular changes. Further studies at genetic level can shed more light on this topic.